Four novel metal coordination polymers directed by 1,1′-dibutyl-4,4′-bipyridinium dibromide (BBP) and their framework dependent luminescent properties - Yue, Jun-Ming; Niu, Yun-Yin; Zhang, Bing; Ng, Seik Weng; Hou, Hong-Wei (Royal Society of Chemistry, 2011)
In our effort to systematically investigate the influence of spacers and terminal groups in structure-directing agent BBP on Ag/I, Pb/I and Cu/SCN inorganic frameworks, four coordination polymers, {[(Ag2I 6)(BBP)2]} (1), {[(Pb6I22)(DMF) 2(BBP)5]} (2), {[Cu2(SCN)4(BBP)]} n (3) and {[Cu4(SCN)6(BBP)]}n (4) have been synthesized in polar organic solvents. Compound 1 is a dimer of [Ag2I6]2-; compound 2 is a hexanuclear oligomer of [Pb6I22]10-; both compound 3 and 4 are infinite Cu(i) supramolecular polymers linked by bridging thiocyanate groups; whereas compound 3 possesses a 1D chain structure, compound 4 exhibits a two-dimensional cubane-based polypseudorotaxane network. All compounds were further characterized with elemental analysis, IR spectra, thermal analysis, and fluorescence properties. © 2011 The Royal Society of Chemistry.